2009
DOI: 10.1007/s00268-009-0205-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Metastatic Lymph Node Ratio in Gastric Cancer Patients

Abstract: The MLR is an important and easy-to-assess prognostic factor that should be considered for staging lymph node metastasis in patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 27 publications
(52 reference statements)
0
24
0
1
Order By: Relevance
“…It is known that the site of the tumour, tumour size and tumour stage, in particular lymph node status, are standard prognostic factors in patients with gastric cancer [27]. Every year a number of new prognostic factors associated with tumour biology-so-called biologic prognostic factorsare proposed.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the site of the tumour, tumour size and tumour stage, in particular lymph node status, are standard prognostic factors in patients with gastric cancer [27]. Every year a number of new prognostic factors associated with tumour biology-so-called biologic prognostic factorsare proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many investigators demonstrated the RPDL was the most intensive category of the nodal metastasis for predication the postoperative OS of gastric cancer patients, owing to its inhibition of the stage migration regardless of the number and the extent of lymph node dissection [28][30]. Nevertheless, the prognostic superiority of the RPDL has been still controversial for many years [8].…”
Section: Discussionmentioning
confidence: 99%
“…Fukuda et al [20] compared the pN category of the UICC/TNM in 1997 with a classification based on the metastatic lymph node ratio in patients who underwent R0 resection using the regression analysis, and identified that the metastatic lymph node ratio is the most important prognostic factor for gastric cancer. The results of univariable and multivariable analyses of potential prognostic factors in this study showed that the rN category was one of the independent prognostic parameters.…”
Section: Discussionmentioning
confidence: 99%